Impact of the 2008 Olympic Games on urban thermal environment in Beijing, China from satellite images. (July 2017) - Cai, Guoyin; Liu, Yang; Du, Mingyi
Highlights: This article evaluated the impact of the 2008 Olympic Games on the spatial expansion of urban heat islands as well as urban size in Beijing City. Most papers about the impact of the games paid more attention on the air quality, the topic in this paper was scarcely reported. A new method was proposed to extract the whole urban boundary by combining GIS and RS technologies. The quantitative value for the minimum ratio of water-pervious to water-impervious surface was given to keep a livable urban environment. Abstract: Beijing has suffered from a rapid development of urbanization in recent years especially since the successful bidding of the 2008 Olympic Games on July 13, 2001 in Moscow. To identify the influence of this paramount sporting event on development of the urban heat island (UHI) effect, this paper examined the spatial expansion of the urban size and UHI effect in Beijing from the years 1999, 2004 to 2008 and 2008 to 2013 using Landsat satellite images. These time spans indicated the process of urbanization in Beijing before and after hosting the 2008 Olympic Games. A new method was proposed to delineate the whole urban boundaries in Beijing governmental area by combining the Remote Sensing (RS) and Geographical information Science (GIS) technologies. The spatial expansion intensity and directions both for urban size and UHI effect were computed and analyzed. By 2013, the urban size of Beijing expanded to more than twice its size in 2008. The sprawl directions for the urban size and the areas with a severe UHI effect were the same, whereas the areas with a severe UHI effect were not enlarged with the increasing urban size. This indicated that the urban development in Beijing after hosting the games was more reasonable which makes the Beijing city be more livable. Statistically, the UHI effect was mitigated when the ratio of areas with water-pervious surfaces to the whole urban region was more than 35%. The urban thermal environment has been improved by increasing the areas of the water-pervious surfaces since hosting the 2008 Beijing Olympic Games.